Архитектор Иван Чарушин - Минин Рудольф Андреевич (Удмуртия, 2020)
Экземпляры: СБ (20200924) / Инвентарный номер: 60101 / Цена: 120.00 / Сис.шифр: 85.11(2Рос.Удм) / Авт.знак: М 61 / ГРНТИ: 18 / ББК: 85.11(2Рос.Удм)